Impacts of Expanding Impervious Surface on Specific Conductance in Urbanizing Streams. Issue 8 (5th August 2019) - Baker, M. E.; Schley, M. L.; Sexton, J. O.
Abstract: Long‐term analysis indicates that progressive salinization of freshwaters is widespread. Although increases are often associated with urbanization, knowledge of chemical dynamics during urbanization is limited and typically drawn from space‐for‐time studies. Thus, the potential role of stream chemistry in sharp biodiversity losses observed at low levels of urbanization is difficult to distinguish from other concurrent factors such as temperature, flow, or sediment. We used a 25‐year annual time series of impervious cover for the Baltimore‐Washington, DC, metropolitan area to interpret long‐term records from 12 watershed‐monitoring stations in the Mid‐Atlantic Piedmont USA from 1986 to 2010 and explore stream conductivity under progressive urbanization. All 12 watersheds experienced variable but monotonic increases in impervious cover, which ranged from <1% to nearly 25% of contributing area. All monitoring stations exhibited elevated specific conductance relative to background concentrations. Proliferation of impervious cover led to seasonal shifts in monthly conductivity maxima, with progressive dominance of winter pulses and diminishing signal from evapotranspirative concentration in late summer. We found consistently steep increases in stream conductivity across years and seasons associated with incremental increases in low (0‐4.5%) levels of watershed impervious cover; moderate to low rates of increase, but distinct seasonal concentrations from 4.5 to 13.8% impervious cover; and increasing predominance of pulses at high levels of impervious cover (>13.8%), particularly when conditioned on winter storm events. Observed patterns may suggest distinct sources and different degrees of hydrologic connection. Despite ubiquitous increases, variability in conductivity trends across space and time underscores the need for more intensive monitoring as urbanization progresses. Key Points: Twenty‐five‐year time series of impervious cover linked to monthly stream conductivity at 12 long‐term monitoring stations in a metropolitan area Conductivity did not rise monotonically with imperviousness but varied in space and time, ramping steeply at levels <5% Trends and seasonal patterns differed with impervious levels, as conductivity became increasing dominated by event‐related signals